2015
DOI: 10.1007/s12666-015-0606-9
|View full text |Cite
|
Sign up to set email alerts
|

Role of Different Fractions of Nano-size SiC and Milling Time on the Microstructure and Mechanical Properties of Al–SiC Nanocomposites

Abstract: High energy ball milling was implemented to produce Al-matrix composites reinforced with 2.5, 5, 10, 15 and 20 wt% silicon carbide (SiC) nano-particles. In this regard, Scanning electron microscopy, X-ray diffraction and microhardness tests were applied to clarify the role of milling time and the percentage of nanometric SiC on structural evolutions and mechanical properties of the composites. An increase in the SiC proportion resulted in accelerating the milling process, leading to faster work hardening rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 31 publications
(45 reference statements)
0
6
0
Order By: Relevance
“…In the past decades, the development of nanocomposites has opened new prospect in different fields to obtain materials with enhanced physical and mechanical properties [36,37]. Because the nano-HAp has greater surface area and higher reactivity as a biomaterial compared with its bulk counterpart, it can provide significant characteristics in several medicinal fields, in particular, dental implant.…”
Section: Dental Implantmentioning
confidence: 99%
“…In the past decades, the development of nanocomposites has opened new prospect in different fields to obtain materials with enhanced physical and mechanical properties [36,37]. Because the nano-HAp has greater surface area and higher reactivity as a biomaterial compared with its bulk counterpart, it can provide significant characteristics in several medicinal fields, in particular, dental implant.…”
Section: Dental Implantmentioning
confidence: 99%
“…The hot pressing conditions were optimized by measuring the relative density [17]. Results demonstrated that 520 MPa pressure and 30 min time is the best condition for achievement of highly relative density (98.2 %), Figure 9.…”
Section: Resultsmentioning
confidence: 99%
“…Several metals and their alloys have been used as matrix in the research works for producing MMCs. The most worked on material is aluminum and its admixtures [7][8][9]. Many research studies suggested the suitability of Al-based composites for structural applications.…”
Section: Introductionmentioning
confidence: 99%